Strategies of Chinese-English culture specific items: the case of translation test from CET 4 and CET 6 - Niu, Chunyuan; Ng, Chwee Fang; Abdul Halim, Hazlina; Mustapha, Nik Farhan (Faculty of Modern Languages and Communication, Universiti Putra Malaysia, 2024)
Culture-specific items (CSIs) constitute a critical component within the realm of cultural translation, particularly evident in the context of China’s widely participated CET-4 and CET-6 (College English Test Band 4 and Band 6). These examinations have garnered increasing scholarly attention due to their substantial influence on language education and international communication. Drawing inspiration from Nida’s (1945) cultural criteria and Newmark’s (1988) translation strategies, this comprehensive study delves into the intricacies of CET-4 and CET-6 CSIs spanning the decade from 2013 to 2023. The findings reveal that diverse types of CSIs necessitate distinct translation strategies, influenced by political, economic, sociocultural factors, and translation purposes. Moreover, a majority of these CSI employ a combination of translation strategies to fulfill their translation objectives. In essence, this study analyzes CSIs in China’s CET-4 and CET-6 English tests, enhancing the understanding of cultural translation and improving the cultural translation skills. It reveals that different CSIs require distinct translation strategies influenced by various factors, providing valuable insights for translators, students and educators.